Diabetic Foot Care Plan - Gordon Dow; The Diabetic Foot Care Plan Working Group (Canadian Journal of Infectious Diseases)
Diabetes mellitus is the number one cause of limb loss in North America, and is associated with growing, unacceptable rates of morbidity, mortality and economic loss. Approximately 80% of these amputations are preceded by the development of foot ulceration. Various disciplines have studied the prevention and management of foot ulceration in those with diabetes. The present care plan was constructed to incorporate the important contributions from these disciplines into practical therapeutic guidelines. The care plan has been divided into three basic sections: assessment, general management and antibiotic therapy. Each of these sections is described in detail and borrows heavily from previous Canadian position papers. Application of the care plan is illustrated by multiple diabetic foot clinical scenarios, which have been categorized according to the Wagner classification.